The Risk Assessment of Genset Installation Project Using Fault Tree Analysis In Indonesia - Khilmy, Akhmad; Irawan, Mohammad Isa; Lidiawaty, Berlian Rahmy (IPTEK Journal of Proceedings Series, 2020)
The XYZ company had a project to install the generator set (genset) in several island in Indonesia. The project was estimated to finish in 10 months, but it delayed up to 20 months. This delayment made the company experience cost overruns. In the other hand, according to Indonesian Ministry of Energy and Mineral Resource (MSDM) in 2016, the electrification in this project area has not reached 100%. The area are including Kalimantan, West Nusa Tenggara (WTB), Papua, Sulawesi and Maluku. The tardiness was caused by the company can't mitigate the project risk optimally. Therefore this research aims to evaluate this genset installation project to assess the risk, thus in the next project the company can avoid project delay and the overruns cost. The research uses Fault Tree Analysis (FTA) in risk assessment to identify the basic event of the project’s problem. First, this research collect the report of the project. Second, this project collect the problems that caused project delay. There are 154 problems found in this research. The FTA method divides the problems found into 13 basic event. The highest risk that triggers problem for this project are from two basic events, which are user error with the probability rate 0,2013 and installation error with the probability rate 0,1494.